(3HOjY GdEfTGA hGdUaGJ aj GdecGJHGJ hGdeQGSdGJs - (3GdncrQej GdebOSj GdMfHdi, eQYj Hf jhSa Hf CHj HcQ Hf CMeO, (B1033 (3g`s
(3ChdgG (B:s
(3bGd eQYj Hf jhSa GdebOSjGdMeO ddg GdPj CcQe GdEfSGfhHYO agPg ETGQGJ jSjQI hVYJgG aj GdecGJHGJhSejJg HOjY GdEfTGAGdHGH GdChd aj eYQaI WQjbI GdecGJjIs
(3BNQgG (B:s
(3Ke fGOi GdeSjQ ddLgGO abJd HGdfUGQi hbJd hCSQ hNQH ef OjGQge eG dG jMUi Ke YGO Edi HZOGO eDjOG efUhQGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 203s
(3eYLe GdeDdajf(B: 3 / 842s
(3EjVGM Gdecfhf(B: 1 / 171s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs